2017
DOI: 10.1177/0025817217706645
|View full text |Cite
|
Sign up to set email alerts
|

Leg massage by mother resulting in fatal pulmonary thromboembolism

Abstract: We report the sudden death of a 23-year-old male with hairline ankle fracture after massage of the leg by his mother. Autopsy confirmed the cause of death as pulmonary thromboembolism due to deep vein thrombosis of the leg veins which was dislodged and travelled to his lungs consequent to the leg massage. The treating doctors did not warn the patient of the risk of developing pulmonary thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The onset of cardiovascular collapse was shortly after leg massage, highly suggestive of thrombus embolization. Unlike most previous case reports of leg massage, concerning induced pulmonary embolism that occurred in previously known cases of deep vein thrombosis in non-pregnant patients [2][3][4], the case presented here is the first case report of leg massage leading to thrombi dislodge with the consequence of severe morbidity in a healthy pregnant woman who had undetected preexisting deep vein thrombosis, which was likely aggravated by physiologic changes during pregnancy. Unfortunately, our patient had not attended antenatal clinic before the event.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The onset of cardiovascular collapse was shortly after leg massage, highly suggestive of thrombus embolization. Unlike most previous case reports of leg massage, concerning induced pulmonary embolism that occurred in previously known cases of deep vein thrombosis in non-pregnant patients [2][3][4], the case presented here is the first case report of leg massage leading to thrombi dislodge with the consequence of severe morbidity in a healthy pregnant woman who had undetected preexisting deep vein thrombosis, which was likely aggravated by physiologic changes during pregnancy. Unfortunately, our patient had not attended antenatal clinic before the event.…”
Section: Discussionmentioning
confidence: 52%
“…Though systematic reviews on the effectiveness of massage therapy have demonstrated positive conclusions, adequate risk-benefit evaluations are not feasible, and several case reports indicate that it is not entirely risk free, though serious adverse events are probably rare [1]. Pulmonary embolism is the most serious consequence of massage, which has rarely been reported [2][3][4]. To the best of our knowledge, this is the first case of traditional massage causing massive pulmonary embolism in a healthy pregnant woman.…”
Section: Introductionmentioning
confidence: 90%
“…It has been recorded that pressure and trauma can dislodge a thrombus leading to a pulmonary embolism. [ 4 5 ] However, it has been rarely recorded that pressure can lead to thrombus formation itself. Upper limb DVT is managed similar to a lower limb DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Since ancient times, massage therapy has been used to promote healing by people of all backgrounds and cultures [32]. In the context of the White Book of Physical and Rehabilitation Medicine (PRM) in Europe, is noted that massage is one of physical agents used in treatment of people with many illnesses [33].This finding has the importance of recognizing the massage as a scientific method for the treatment of multiple diseases.…”
Section: Discussionmentioning
confidence: 99%